Experimental Study on the Utilization of Cement Kiln Dust for Ground Modification - Talal O. Al-Refeai; Awad A. Al-Karni (Journal of King Saud University: Engineering Sciences)
In recent years, use of various waste products in ground construction and modification has gained considerable attention worldwide in view of increasing costs of waste disposal, and environmental constraints. One of these waste products is the cement kiln dust, which is a by-product of Portland cement manufacturing process. It is generated from burning the raw materials in a rotary kiln to produce clinker. Generally, for each one ton of clinker, a typical kiln generates around .06–.07 ton of cement kiln dust.In this study, first, an overview of physical, chemical, and mechanical properties of kiln dust that related to utilization in ground modification are presented. These properties are presented for different samples collected from cement manufactures in central, eastern, and southern regions of the Kingdom of Saudi Arabia. Second, the effect of adding different percentage of cement kiln dust on the engineering properties of three different problematic soils in the central region of Saudi Arabia was investigated. The results show significant improvement in their engineering properties. The plasticity index and liquid limit of clays decrease significantly as the percentage of added cement kiln dust increases. The optimum moisture content and the maximum dry density of dune sand increase as the added cement kiln dust increases. The unconfined compressive strength was found to increase substantially during the first seven days. The permeability of treated dune sand was found to reduce significantly better than that of treated soil with cement. And finally the collapse potential of treated collapsing soil with cement kiln dust was reduced significantly.